2005
DOI: 10.1049/el:20057841
|View full text |Cite
|
Sign up to set email alerts
|

Single fundamental mode photonic crystal vertical cavity laser with improved output power

Abstract: The single fundamental mode output power of photonic crystal vertical cavity lasers is improved by varying sizes of oxide apertures and defect lasing apertures. A maximum output power of 3.1 mW in the fundamental mode has been achieved with a new fabrication process that involves only focused ion beam etching to create holes in selectively oxidised VCSELs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…These devices have strong potential for leaving laboratories into the market due to their unique properties, which make them a perfect choice for many applications. These properties include a stable single-mode operation [1,2,3], high-speed modulation [4,5,6] and polarization control [7,8]. Typical PC-VCSELs consist of a classical VCSEL cavity surrounded by Distributed Bragg Reflectors (DBRs) of high reflectivity, with lateral photonic crystal structure which provides lateral light confinement.…”
Section: Introductionmentioning
confidence: 99%
“…These devices have strong potential for leaving laboratories into the market due to their unique properties, which make them a perfect choice for many applications. These properties include a stable single-mode operation [1,2,3], high-speed modulation [4,5,6] and polarization control [7,8]. Typical PC-VCSELs consist of a classical VCSEL cavity surrounded by Distributed Bragg Reflectors (DBRs) of high reflectivity, with lateral photonic crystal structure which provides lateral light confinement.…”
Section: Introductionmentioning
confidence: 99%
“…4.11). GaAs-based PhC-VCSELs have reached a singlemode power of 3.1 mW (MSR > 30 dB) at 850 nm [39], 5.7 mW (MSR > 35 dB) at 990 nm [40] and 1.7 mW (MSR > 30 dB) at 1.3 µm [41]. A particular problem for such PhC-VCSELs is the increased optical loss and electrical resistance caused by the deep holes, leading to relatively high threshold currents and low power efficiency.…”
Section: Inherently Single-mode Vcselsmentioning
confidence: 99%
“…The PhC VCSEL structure investigated here is defined by: R A = 4 μm, a/L = 0.5, which have been chosen to assure high modal gain [14] and clear discrimination between the fundamental and first order modes [15]. The ratio a/L = 0.5 has been assumed as the mean value used by other authors [5,6,[35][36][37][38] and has been found to lead to low lasing temperature [16]. The funneling of carriers and their uniformity in the active region is assured by a proton-implanted tunnel junction placed in the node position of the standing wave (Fig.…”
Section: The Model Our Multi-physical Model Comprises a Three-dimensimentioning
confidence: 99%